Crosslinking: methodological approaches and application in ophthalmology - I. B. Medvedev; V. Ju. Evgrafov; N. N. Dergacheva (Oftalʹmologiâ, 2016)
Crosslinking of the cornea was developed at the end of the last century and radically changed approaches to the treatment of progressive corneal ectasia. To achieve the strengthening of the corneal tissue irradiation with ultraviolet light And is combined with the use of Riboflavin. Riboflavin plays a role of a photosensitizer in the process of photopolymerization and ultraviolet irradiation increases the formation of inter — and intrafibrillary covalent bonds. Standard Protocol operation involves the scarification of epithelium, a 30‑minute application of 0.1 % solution of Riboflavin with subsequent 30 min. irradiation with ultraviolet light with A wavelength of 370 nm and 3 mW / cm2. The lack of effect of routine procedures is defined as the increase in refractive power of the cornea by 1 Diopter. after treatment and observed in 8.1‑33.3 % of cases. A relatively frequent complication of the standard procedure of crosslinking (10‑90 %) is corneal haze. A number of cases of infectious keratitis, including bacterial, protozoan and fungal forms is registered. Rare complications after standard procedure of crosslinking are diffuse lamellar keratitis, melting corneal and endothelial-epithelial dystrophy. After instillation of Riboflavin its diffusion in the corneal stroma is limited by a dense contacts between epithelial cells, resulting in crosslinking often resort to preliminary scarification of epithelium. However, this manipulation is the cause of the complications of crosslinking, as intra — and postoperative pain, infectious keratitis and lethargic regeneration of the epithelium. The permeability of the epithelium for Riboflavin can be enhanced in several ways, for example, modifying physico-chemical properties of Riboflavin molecules or increasing the permeability of the epithelium, for example, by instillation of a 40 % strength solution of glucose. It was shown that the conducting electrophoresis with Riboflavin for 5 minutes, allows to reach a concentration in the cornea sufficient to conduct the crosslinking. There have also been attempts to reduce the time of the operation of crosslinking by increasing the power of irradiation of cornea with ultraviolet light. In single studies reported on the successful use of corneal crosslinking combined with photorefractive keratectomy and intracorneal the rings, as well as for the treatment of infectious keratitis and endothelial-epithelial dystrophy of the cornea.